2017
DOI: 10.9790/3013-0704014862
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal plants possessed antioxidant and free radical scavenging effects (part 3)- A review

Abstract: Abstract:-Antioxidants are substances that remove, prevent or delay oxidative damage to a target molecule. Therefore, an antioxidant may act to control the level of free radicals to counteract oxidative damage. The effects of medicinal plants in prevention and treatment of many diseases have been widely attributed to their antioxidants activities. This review was designed to highlight the antioxidant effects and free radical scavenging activity of medicinal plants as a third part of our previous reviews.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…In the estimation of DPPH free radicals scavenging activities, a positive correlation was observed between the flavonoid and phenolic content of the D. metel extracts [8,42]. Maximum DPPH scavenging activity of methanolic seed extracts of D. stramonium was found to be 59.50% at a concentration of 60 µg/mL with IC 50 value of 94.87 µg/mL; similarly, the maximum superoxide radical scavenging activity was 53.17% at a concentration of 60 µg/mL, while maximum scavenging activity of hydroxyl radical was 57.88% at concentration of 30 µg/mL with IC 50 value of 39.59 µg/mL [41].…”
Section: Antioxidation Activitiesmentioning
confidence: 94%
See 1 more Smart Citation
“…In the estimation of DPPH free radicals scavenging activities, a positive correlation was observed between the flavonoid and phenolic content of the D. metel extracts [8,42]. Maximum DPPH scavenging activity of methanolic seed extracts of D. stramonium was found to be 59.50% at a concentration of 60 µg/mL with IC 50 value of 94.87 µg/mL; similarly, the maximum superoxide radical scavenging activity was 53.17% at a concentration of 60 µg/mL, while maximum scavenging activity of hydroxyl radical was 57.88% at concentration of 30 µg/mL with IC 50 value of 39.59 µg/mL [41].…”
Section: Antioxidation Activitiesmentioning
confidence: 94%
“…Analysis of Datura plant extracts for antioxidant characteristics revealed its ability to cure various health disorders, including cancers, since antioxidants are known to inhibit cell damage, the general pathway for cancers, aging, and several other diseases [41]. The antioxidant capacity of leaf extracts in different solvents, estimated by various in vitro methods, including hydroxyl radical scavenging activity, DPPH (2,2-diphenyl-1-picrylhydrazyl) scavenging activity, superoxide radical scavenging activity, β-carotene bleaching activity, and reducing power assay, revealed that chloroform extract of leaves possessed maximum concentration-dependent antioxidant activity [42,43]. The IC 50 value of methanolic and hydroalcoholic seed extracts of D. metel recorded using the DPPH model showed that hydroalcoholic extract possesses slightly higher antioxidant activities (IC 50 of 25.78 µg/mL) than methanolic seed extract (IC 50 of 28.34 µg/mL) [7,42].…”
Section: Antioxidation Activitiesmentioning
confidence: 99%
“…Various antioxidant systems are produced by the body for ROS detoxi ication. This disparity between the free radicals and antioxidants are supposed to cause many in lammatory pathologies (Al-Sna i, 2017). Valuation of the levels of antioxidant enzyme activities such as those of CAT, SOD, and glutathione help to measure the antioxidant status of the extract (Cimen et al, 2003;Babaee et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Dermatology: It has been deeply studied that plants provide beneficial effects to humans due to their antimicrobial 3,13,44 , antioxidants [45][46][47] , among others properties, which are attributed to their secondary metabolites 48 . However, phytochemical effectiveness on skin can be conditioned by environment characteristics, compound degradation rate or other physicochemical drawbacks 49 .…”
Section: Anti-inflammatory and Antioxidant Activitymentioning
confidence: 99%